Field reports form, contributed by Peter C. Petersen, spring 1985 - Petersen, Peter C.et al (1985)
The field notes list various birds spotted by Petersen and others in eastern Iowa and includes comments on the weather. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed